Attitudes Toward Future Japanese Families among Japanese University Students : Tradition, Ideals and Stigmas - Heikkinen, Milla (My University, 2019)
This MA thesis studies the attitudes of university students toward family ideals during the heightened demographic issues present in society in 21st century Japan. The ie ideology, the traditional conceptualization of family with a patriarchal head of house and dutiful wife who cares for the children and husband’s parents in one household, has created remnants that have furthered already present stigmatizations of nontraditional family formats, heightening the need for further research as family ideals are rapidly changing. This research study sets out to explore the attitudes of university students who have the potential to be the future generation of parents, to gather information on family-related ideals as a way to formulate a comprehension of the changing family ideals that are in part causing the demographic crisis. Through the use of qualitative research methods, the research results indicate that there is not just one culprit towards declining birthrates, but that there are several in that the changing family ideals have created multiple ideal families as suggested by university students. These ideals include, but are not limited to, multigenerational households, nuclear households, and single person households, with or without marriage and children, clearly distinguished from previous generations. Family has also begun to incorporate non-blood related individuals into the embodiment of family, completely changing the traditional concept for family as mandated by ie ideology. With the inclusion of more individualistic tendencies that are subsequently delaying marriage and children until later, perhaps even indefinitely, as Japanese youth are dedicating more effort towards education, careers and individual indulgences. These changing perspectives on family have created attitudes that are normalized to have few to no children, due to the presence of nontraditional family tendencies visible within society, thus, then creating divergent attitudes for family formation. These results incorporate the understanding of family from the perspectives of university students to better understand the fertility crisis, not from an economic perspective, but rather from a social science and sociology perspective. The inclusion of young adult ideals and views helps to further the research on the fertility issue, whilst also providing insight into the changing concept of family in the Japanese context.
Keywords: family ideals, Japanese families, Japanese households, family-related stigma, single parenthood, illegitimacy, nontraditional families, traditional families, university students, individual collectivism, fertility, declining population, Japan.